Markets in fashion : a phenomenological approach - Aspers, Patrik, 1970- (Routledge studies in business organization and networks ;, 2006)
Interest in contemporary cultural industries has grown in the past decade, as they take on a greater significance in our increasingly consumer-led society. Focusing on the world of fashion photography, this book presents an interdisciplinary approach in which this and other aesthetic markets, such as advertising, modelling, art, music and more, can be viewed. The main thrust of this groundbreaking book, is in developing a theory for these cultural markets, characterized by insecurity, and where status and aesthetic diversity generate order and price differentiation. In these industrie.